The Effect of Adding Carrot Powder, Dragon Fruit, Secang Wood, and Telang Flowers on the Physicochemical and Sensory Characteristics of Milk Ice Cream - Setyawati, Awalia Putri; Daffarrel, Reyhan; Azizah, Fitri Nur; Ananta, Maghriza Dhafa; Setyawardani, Triana; Sumarmono, Juni; Arkan, Naofal Dhia; Fadhlurrohman, Irfan (Faculty of Animal Science Universitas Brawijaya, 2025)
This study aims to evaluate the effect of the addition of carrot powder, dragon fruit, secang wood, and telang flowers on the physicochemical and sensory characteristics of milk ice cream. A Complete Random Design (CRD) with four treatments and five repeats was used to observe color, overrun, pH, melting time, texture, and organoleptic parameters. The results show that the addition of natural ingredients has a significant influence on several parameters. Colour and texture showed noticeable differences, with the carrot (P1) treatment having high lightness (62.39±3.89) and with secang wood (P3) treatment having high hardness (509.34 N), while dragon fruit (P2) was preferred in organoleptic tests. Overrun and melting time don't show any noticeable difference (p > 0.05), but overall values are below home industry ice cream standards. The addition of natural ingredients such as dragon fruit and telang flower lowers the pH, influenced by the anthocyanin content. In conclusion, natural ingredients can improve the visual characteristics and sensory preferences of ice cream, but it need optimization to meet industry quality standards.